2019
DOI: 10.1002/job.2353
|View full text |Cite
|
Sign up to set email alerts
|

Information, beliefs, and motivation: The antecedents to human resource attributions

Abstract: Summary Despite significant interest in the attributions employees make about their organization's human resource (HR) practices, there is little understanding of the antecedents of HR attributions. Drawing on attribution theory, we suggest that HR attributions are influenced by information (perceptions of distributive and procedural fairness), beliefs (organizational cynicism), and motivation (perceived relevance). We test a model through a two‐wave survey of 347 academic faculty in the United Kingdom, examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
113
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(118 citation statements)
references
References 76 publications
5
113
0
Order By: Relevance
“…For example, research indicates that commitment attributions are positively related to employee commitment to the organization (Fontinha, Chambel, & De Cuyper, 2012) and job satisfaction (Nishii et al, 2008), while control attributions are positively related to work overload and emotional exhaustion (Shantz et al, 2016). Recently, Hewett, Shantz, and Mundy (2019) examine the antecedents of HR attributions, applying attribution theory (Kelley & Michela, 1980) to the influence of information (perceptions of distributive and procedural fairness), beliefs (organizational cynicism), and motivation (perceived relevance) on employees' interpretation of employer's intent behind a workload model. The results of a study of 347 UK academics show that fairness and cynicism are important for the formation of HR commitment attributions; these factors also interact in such a manner that distributive fairness buffers the negative effect of cynicism.…”
Section: Empirical Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, research indicates that commitment attributions are positively related to employee commitment to the organization (Fontinha, Chambel, & De Cuyper, 2012) and job satisfaction (Nishii et al, 2008), while control attributions are positively related to work overload and emotional exhaustion (Shantz et al, 2016). Recently, Hewett, Shantz, and Mundy (2019) examine the antecedents of HR attributions, applying attribution theory (Kelley & Michela, 1980) to the influence of information (perceptions of distributive and procedural fairness), beliefs (organizational cynicism), and motivation (perceived relevance) on employees' interpretation of employer's intent behind a workload model. The results of a study of 347 UK academics show that fairness and cynicism are important for the formation of HR commitment attributions; these factors also interact in such a manner that distributive fairness buffers the negative effect of cynicism.…”
Section: Empirical Findingsmentioning
confidence: 99%
“…In sum, in comparison to the 'what' and 'how' of employee perceptions, research on the 'why' is less developed (Sanders, Guest, & Rodrigues, 2017). One area where research is especially needed is the determinants of HR attributions (Hewett et al, 2019). Many studies have identified multiple types of HR attributions and explored their impact on employee outcomes; however, knowledge is limited on how such employees HR attributions are formulated.…”
Section: Empirical Findingsmentioning
confidence: 99%
“…(2019) that a broader view which is not only focused on employee attributions (Hewett et al . 2018, 2019; Nishii et al . 2008; Sanders et al .…”
Section: Contributions and Concluding Wordsmentioning
confidence: 99%
“…In the fourth paper, Hewett, Shantz, and Mundy () apply attribution theory to the human resource management context to examine the antecedents of employees' attributions about human resource management practices. Hewett et al tested their model with multiwave data from 347 academic faculty working in the United Kingdom.…”
Section: An Overview Of the Papers In This Special Issuementioning
confidence: 99%
“…Altogether, these five papers extend attribution theory in numerous areas of critical importance, including micro contexts and macro contexts in organizational behavior, leadership, human resource management, and strategic management. The varying study designs used across Munyon et al's (), Hewett et al's (), and Sun et al's () papers illuminate the myriad of opportunities to empirically examine attributions. Additionally, the cross‐cultural findings from employee respondents in organizations located in China, Great Britain, and the United States show that attributions apply to a range of contexts.…”
Section: An Overview Of the Papers In This Special Issuementioning
confidence: 99%